The Association of Glucose Variability and Home Discharge Among Survivors of Critical Illness Managed With a Computerized Decision-Support Tool for Glycemic Control. (March 2014) - Oud, Lavi; Spellman, Craig
In–intensive care unit (ICU) glucose variability (GV) is associated with increased mortality. However, the impact of GV on hospital survivors' morbidity and associated changes in destination at time of hospital discharge are unknown. We studied a retrospective patient cohort in a medical/surgical ICU, requiring insulin infusion, using computer-guided insulin dosing software. Standard deviation (GluSD ) and coefficient of variation (GluCV ) were used as GV measures. We examined rates of home discharge (H) in the whole cohort and selected subgroups across GV quartiles, between patients with and without H, determinants of H, and determinants of GV and its association with patients' ICU length of stay (LOS). A total of 351 patients met study criteria. The association of GV and H varied among examined subgroups. H increased with GV quartile (GluSD ; P = .004). GV was higher in patients with H than non-H (GluSD 36.1 vs 30.0 mg/dl, respectively; P = .002). Increased GV was not a predictor of reduced H on multivariate analysis. GV was inversely associated with patients' ICU LOS in all examined subgroups. Increased number of hypoglycemic events and time to attain target glycemia were independent predictors of reduced H. GV was not associated with adverse impact on H in the present cohort, and its prognostic impact should be considered in the context of ICU LOS of examined patient populations. Further studies are needed to examine the morbidity effects of GV and other glycemia-related measures among hospital survivors of critical illness across varying ICU populations, glycemic control approaches, and glycemic targets.